2011
DOI: 10.1002/poc.1870
|View full text |Cite
|
Sign up to set email alerts
|

Generation of triplet carbenes by oxidation of an allene compound

Abstract: Computational analysis on the dicationic species generated upon two‐electron oxidation of the corresponding allenic compounds bearing two thioxanthene (7a) or two acridene (7b) moieties indicated that the ground‐state multiplicity would be of the triplet state (ΔEST = ECS − ET = 12.6 and 14 kcal/mol, respectively). Under this premise, oxidation reactions of 7a and 7b were carried out. In the case of 7b, oxidation with (p‐BrC6H4)3N•+SbCl6− gave a dimer (13), which could be presumed to have formed by dimerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The two-electron oxidation of 5a resulted in the formation of dimer 7 (Scheme 4). [8] This result indicated that the intermediate was carbene 6a. Furthermore, trapping experiments with tetramethylpiperidine N-oxide (TEMPO) to afford the carbonyl compound 8a, and theoretical calculations suggested that intermediate 6a had a triplet ground state.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The two-electron oxidation of 5a resulted in the formation of dimer 7 (Scheme 4). [8] This result indicated that the intermediate was carbene 6a. Furthermore, trapping experiments with tetramethylpiperidine N-oxide (TEMPO) to afford the carbonyl compound 8a, and theoretical calculations suggested that intermediate 6a had a triplet ground state.…”
Section: Introductionmentioning
confidence: 90%
“…The nitrogen‐bridged allenes were expected to oxidize more easily than the analogous sulfur‐bridged system. The two‐electron oxidation of 5a resulted in the formation of dimer 7 (Scheme ) . This result indicated that the intermediate was carbene 6a .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Two-electron oxidation of 5a afforded dimer 7 as the product, which could be assumed to have arisen via 6a. Successful trapping of the reactive intermediate by tetramethylpiperidine N-oxide (TEMPO) suggested the intermediacy of triplet carbene 6a.…”
Section: Introductionmentioning
confidence: 99%
“…Our method was based on the two-electron oxidation of allenic precursors bearing two thioxanthene or acridene moieties. [7][8][9] Thus, we attempted the oxidation of allenic compound 3 bearing two dimethoxythioxanthene moieties [10] that was previously reported by our group (Scheme 2). However, the oxidation of 3 did not furnish a stable triplet carbenic species but instead provided ketal 4, likely via a singlet ground-state carbene.…”
Section: Introductionmentioning
confidence: 99%